Importance of micronutrients in the oral cavity - Ranjit Rajesh; Takalloabdal Sadaf; Galchenko Alexey V. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2021)
Introduction: Micronutrients play a potent role in the functioning of the different systems of the organism. It is necessary to sustain an adequate status of the micronutrients for maintaining the optimal condition of the oral cavity. The aim: Toemphasize the importance of different micronutrients for the normal functioning of the oral cavity, as well as their influence on the occurrence of various diseases of the soft and hard tissues of the oral cavity. Conclusion: Micronutrients such as vitamin C, B9 and E, calcium, zinc, copper and iron have a role in development so as anti-inflammatory and antioxidants properties Deficiency of certain micronutrients plays an important role in the development of periodontitis and caries. People with chronic inflammatory bowel disease, as well as children, pregnant and breastfeeding women, are usually deficient in these vitamins and therefore often susceptible to the development of inflammatory changes in soft tissues of oral cavity , periodontitis and caries.